APLIKASI PROMOSI PARIWISATA BERBASIS WEB DENGAN MENGGUNAKAN FRAMEWORK CODEIGNITER - Dandy Pramudya, (2020)
Tourism promotion activities are very important activities for the Pandeglang District Tourism Office. Promotional activities are needed to introduce a variety of available tourism, especially tourism in the Pandeglang Regency. The promotion activities are expected to increase the attractiveness of local and foreign tourists to visit tourist attractions in the Regency of Pandeglang whose ultimate goal is to achieve the target of local and foreign tourists. To achieve these objectives the Pandeglang District Tourism Office requires a special application or platform to promote tourism that can attract local and foreign tourists. The purpose of this study is to create a tourism promotion application that is useful for promoting both tourism and tourism activities so that the tourism visit of Pandeglang Regency has reached a predetermined target. The method used in the design of this system uses the Incremental method, where, there are five stages carried out on the Incremental method, namely communication, planning, modeling, coding, and deployment. The output of this research is in the form of a web-based tourism promotion application designed using a CodeIgniter framework. With this tourism promotion application, it is expected that tourists can easily get information about tourism in Pandeglang Regency and can share reviews and photos of Pandeglang tourism they have visited.